Digital Chromoendoscopy With i-Scan for In Vivo Prediction of Advanced Colorectal Neoplasia: A Multicenter Study. Issue 10 (November 2016) - Albrecht, Heinz; Nägel, Andreas; Tasdelen, Hüseyin; Rath, Timo; Grauer, Martin; Vieth, Michael; Neurath, Markus F.; Neumann, Helmut
Abstract : Background: Recent studies have analyzed the potential of advanced endoscopic imaging techniques for differentiating hyperplastic and adenomatous colorectal lesions. Latest endoscopic resection techniques now also allow for treatment of more advanced staged lesions including treatment of early cancerous lesions. Aims: To assess the potential of the i-scan technology to differentiate between adenomatous polyps and advanced staged neoplasia. Methods: Consecutive patients undergoing colonoscopy at a tertiary referral center were included. After a dedicated training, participating endoscopists underwent a review of 298 unknown images of colonic lesions to assess colorectal lesion histology. Results: Overall accuracy for prediction of advanced staged neoplasia was 92.2% (sensitivity: 94.2%, specificity 90.9%). The positive and negative predictive values were calculated as 87.5% and 95.9%, respectively. The κ-value for differentiating adenomatous polyps and advanced staged neoplasia was 0.8193 (0.7894 to 0.8492). Intraobserver agreement was calculated with a κ-value of 0.9301 (0.8875 to 0.9727). Conclusions: Accurate interpretation of i-scan images for prediction of advanced colorectal neoplasia can successfully be performed even by nonexpert endoscopists with a high overall accuracy and excellent interobserver agreements.